Usia dan obesitas berhubungan terhadap terjadinya penyakit benign prostatic hyperplasia di RSUP Sanglah Bali periode januari 2014 sampai desember 2014 - Kadek Devi Ari Frasiska; Anak Agung Gde Oka (E-Jurnal Medika Udayana, 2018)
Benign protastic hyperlasia (BPH) is a disease affecting the prostate gland where the state of enlarged prostate will impede the flow of urine and cause symptoms. BPH is commonly suffered by middle aged to elderly men. There are many risk factors regarding to this disease, such as age and obesity. Therefore, the aims of this research to describe the relationship between age and obesity with the incidence of BPH. This research used descriptive analytic design and the samples were taken using consecutive sampling. Subject and place of research are men aged >40 who visited polyclinics urology department and were hospitalized in Sanglah Hospital during January until December 2014. Results of this research are from 138 samples in term of age, there were 65 elders, 66.2% suffered from BPH, while 33.8% did not. Out of 73 adults, 41.1 % suffered from BPH and 58.9% did not. After being analyzed using chi-square, the result showed that age had significant correlation to the occurrence of BPH with p=0.003. However, regarding to obesity factor, there were 98 persons with obesity, 49% suffered from BPH, and 51% did not. Meanwhile, 40 persons who were not obese, as many as 41.1% suffered from BPH, and 58.9% did not. After being tested using chi-square, the result showed that there was no significant correlation between obesity and BPH with p=0.184. Conclusion of this research are age is the risk factors of benign prostatic hyperplasia , whereas obesity is not a risk factor of BPH. Keywords: Benign prostatic hyperplasia, age, obesity